ChemInform Abstract: Synthesis of the Layered Quaternary Uranium‐Containing Oxide Cs2Mn3U6O22 and Characterization of Its Magnetic Properties. Issue 32 (August 2015) - Read, Cory M.; Gordon, Elijah E.; Smith, Mark D.; Yeon, Jeongho; Morrison, Gregory; Whangbo, Myung‐Hwan; zur Loye, Hans‐Conrad
Abstract Single crystals of the title compound are prepared by reaction of MnCl2 and U3O8 in a CsCl flux (alumina crucible, 900 °C, 9 h, 40% yield).